Effect of plant growth regulators on flowering and fruit yield of cucumber (Cucumis sativus cv. Malini) in Chitwan, Nepal - Sapkota, B.; Dhital, M.; Shrestha, B.; Tripathi, K. M. (Journal of Agriculture and Forestry University, 2020)
An experiment was done at Rambagh, Chitwan during March to May 2018 with the objective to evaluate the effect of plant growth regulators on growth, flowering and yield of cucumber (Cucumis sativus.) cv. Malini. The experiment consisted of nine treatments viz., control (no spray), silver nitrate 250 ppm spray, ethephon 250 ppm spray, gibberellic acid (GA3) 300 ppm spray, napthalene acetic acid (NAA) 50 ppm spray, silver nitrate 500 ppm spray, ethephon 250 ppm spray, gibberellic acid (GA3) 500 ppm spry, and napthalene acetic acid (NAA) 100 ppm spray; each treatment was replicated thrice. Findings revealed that use of plant growth regulators significantly affected growth, flowering and fruit yield of cucumber. The highest plant height was measured for GA3 300 ppm spray whereas lowest plant height was measured for NAA 100 ppm spray. Likewise, GA3 300 ppm spray had produced highest number of lateral branches. On the other hand, highest number of male flower was recorded in control, but highest number of female flower was recorded for ethephon 250 ppm spray whereas it was lowest for control (14.00). The highest and lowest fruit length was recorded if GA3 500 ppm and ethephon 250 ppm were sprayed, respectively. Likewise, the highest fruit numbers per plant was recorded in GA3 300 ppm application whereas the control had the lowest number of fruit produced. The highest fruit yield was produced from the application of GA3 300 ppm (109.7 t/ha) while the lowest fruit yield was recorded in control (40.53 t/ha). The B: C ratio was high in GA3 300 ppm (4.37) application as well. These results indicate the benefit of spraying GA3 300 ppm to have a better performance and fruit yield of cucumber compared to the other treatments with varied concentrations of NAA and GA3.